Permisos transables frente a la introducción de un combustible limpio: estudio de caso para PM-10 y NOx en Santiago, Chile - O’Ryan, Raul; Bravo, Rodrigo (Estudios de Economía, 2016)
Beginning in 1990 a compensation system for PM-10 emissions from point sources was implemented in Santiago, equivalent to a suboptimal emission permit system (EPS). The objective of the system was to reduce compliance costs and to prevent emissions from new sources, forcing them to compensate all emissions with existing sources. The system basically did not operate until 1997, year in which natural gas –a clean fuel– was introduced into Santiago. In this context, this paper examines the following questions: What is the impact of the introduction of natural gas in the applicability of tradeable permits for PM-10 and NOx? Are they justified or are the efficiency gains so small that direct regulation is preferable? The efficiency gains associated to an optimal ambient permit system (APS) are quantified and compared to the simpler EPS. Finally control cost functions are developed for Santiago for fixed point sources and presented in detail.